Tingkat Adopsi Pengelolaan Tanaman Terpadu (PTT) di Kecamatan Insana Utara - Suri, adenala odilia suri; Joka, Umbu; tabenu, Oktovianus (LPPM Universitas Malikussaleh - Indonesia, 2025)
The use of agricultural technology in rice cultivation in North Insana Kecamatan is still very rudimentary. To increase rice productivity, farmers have attempted to develop integrated crop management (ICM) techniques, a series of techniques that can be adapted to local climatic conditions. This study involved 95 respondents from rice farmers in North Insana District. Data analysis used a struges analysis tool. The results showed that the average quality of integrated crop management (ICM) components among farmerJurnal Agrifos reached 43%. This value is considered low, indicating that few farmers have adopted the quality of integrated crop management (ICM) components, such as the use of easy-to-seed seedlings, the number of seedlings per hole, and harvesting according to the age of New Superior Varieties (VUB).